2021
DOI: 10.1002/bit.27845
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the potential of engineering polygalacturonase‐inhibiting protein as an ecological, friendly, and nontoxic pest control agent

Abstract: In plants, polygalacturonase-inhibiting proteins (PGIPs) play critical roles for resistance to fungal disease by inhibiting the pectin-depolymerizing activity of endopolygalacturonases (PGs), one type of enzyme secreted by pathogens that compromises plant cell walls and leaves the plant susceptible to disease. Here, the interactions between PGIPs from Phaseolus vulgaris (PvPGIP1 and PvPGIP2) and PGs from Aspergillus niger (AnPG2), Botrytis cinerea (BcPG1 and BcPG2), and Fusarium moniliforme (FmPG3) were recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 77 publications
(124 reference statements)
1
14
0
Order By: Relevance
“…The much shorter length of these proteins indicated they could be the result of genetic truncations. However, genetically truncated PGIP s encoding proteins that are even one-third the size of the full length polypeptide can have the same activity against some pathogen PGs (Chiu et al 2021). Thus, the shorter GmPGIP s were included in subsequent bioinformatics analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The much shorter length of these proteins indicated they could be the result of genetic truncations. However, genetically truncated PGIP s encoding proteins that are even one-third the size of the full length polypeptide can have the same activity against some pathogen PGs (Chiu et al 2021). Thus, the shorter GmPGIP s were included in subsequent bioinformatics analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, expression of PGIP3 from soybeans ( Glycine max ) in tobacco has been shown to inhibit the growth of pathogenic Sclerotinia sclerotiorum, Fusarium moniliforme, B. aclada, A. niger, Collectotrichum acutatum, and F. graminearum [ 141 , 142 ]; and expressing PGIP2 from lima beans ( Phaseolus lunatus ) in tobacco also delayed growth of Collectrichum lupini , B. cinerea , F. moniliforme , and A. niger [ 143 ]. Recently, it is also found that truncated PvPGIP2 with only the optimal docking area retains similar level of inhibitory activities towards PGs from A. niger and B. cinerea to the full-length PvPGIP2 [ 144 ]. Yeast strains secreting full-length or truncated PvPGIP2 with the Ost 1 signal peptide were also able to reduce fungal growth and delay sporulation by 1–2 days [ 144 ].…”
Section: Other Proteinsmentioning
confidence: 99%
“…Recently, it is also found that truncated PvPGIP2 with only the optimal docking area retains similar level of inhibitory activities towards PGs from A. niger and B. cinerea to the full-length PvPGIP2 [ 144 ]. Yeast strains secreting full-length or truncated PvPGIP2 with the Ost 1 signal peptide were also able to reduce fungal growth and delay sporulation by 1–2 days [ 144 ]. Although the function of PGIPs when applied exogenously on plants has not been reported, this group of proteins is still considered as a promising candidate to be developed into an eco-friendly fungal control agent.…”
Section: Other Proteinsmentioning
confidence: 99%
“…The seven OsPGIPs are all hydrophobic proteins, with good fat solubility, transmembrane structure, extracellular localization, and multiple N-glycosylation sites, making these proteins insoluble when expressed in E. coli [26]. The exposed LRR motif is critical for the affinity and specificity of PGIP [25][26][27][28].…”
Section: Structural Characteristics Of Pgip Proteinmentioning
confidence: 99%
“…The PGIP anti-disease effect has been confirmed in a series of in vivo experiments. PGIP-mediated fungi resistance has been shown in various important cash crops, such as grapes [57,58], papaya [59], potatoes [51], alfalfa [15], cotton [60], green beans [6,28,61], tomatoes [62], peas [63], mandarin orange [64], tobacco [65], and Arabidopsis [66]. PGIP expression does not affect plant phenotype or inhibit plant growth in sugar beet [67] or tobacco [67].…”
Section: Application Of Pgip In Plant Disease Resistance Genetic Engineeringmentioning
confidence: 99%